Planirovanie trenirovochnogo protsessa plovtsov na osnove nepreryvnogo kontrolya serdechnogo ritma - Solomina, T. V.; Vovchenko, L. I. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The aim of this work is the investigation of possible individual corrections of the training process on the base of the adaptation process in young elite swimmers in the special training period.